Milk as a Non-Invasive and Alternative Sample for Serum in the Diagnosis of Animal Toxoplasmosis: A Systematic Review - Tooran Nayeri; Shahabeddin Sarvi; Rohallah Abedian; Shaban Gohardehi; Seyed Abdollah Hosseini; Ahmad Daryani (Tehran University of Medical Sciences, 2022)
Background: Toxoplasmosis is one of the most important zoonotic parasitic diseases worldwide with a high impact on human and animal health. Body fluids such as milk are used to diagnose many parasitic diseases, including toxoplasmosis. Therefore, this study aimed to investigate the role of milk as a non-invasive and alternative sample for serum in the diagnosis of animal toxoplasmosis. Methods: Five English-language databases (ScienceDirect, PubMed, ProQuest, Scopus, and Web of Science) were explored for published articles before Dec 2020. Results: In total, 42 out of 2256 published articles were included in this systematic review. In 21 articles, serum and milk samples were evaluated simultaneously with serological or molecular tests, and the results were compared. The results of descriptive studies and a review of nine experimental studies showed that milk could be used as a non-invasive and alternative sample for the serum in the diagnosis of toxoplasmosis. Conclusion: Due to the relatively high prevalence of Toxoplasma gondii (T. gondii) infection in milk, consumption of raw milk from infected animals can be a potential source of human infection and a significant threat to public health. On the other hand, due to the ease and cheapness of collecting milk samples, the use of milk is recommended for the diagnosis of toxoplasmosis.